IMPLEMENTASI MODEL PEMBELAJARAN PROBLEM BASED LEARNING PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI DI SMP NEGERI 2 KEDUNGBANTENG - Soimatun Nazia, Ana; Rohman, Mujibur (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2025)
The Problem Based Learning model is one of the learning innovations recommended in the independent curriculum. The implementation of this study aims to examine and describe the application of the Problem Based Learning learning model in the subjects of Islamic Religious Education and Character Education at SMP Negeri 2 Kedungbanteng with a focus on improving student understanding. This study uses a descriptive qualitative research method with a field approach. Data collection was carried out using direct observation, interviews, and document searches at the research location. The subjects involved in this study included Islamic Religious Education teachers and grade VIII students. From this study, it can be concluded that the implementation is carried out through three stages, including: 1) Planning stage, the process of implementing the Problem Based Learning learning model, teachers prepare teaching modules as guidelines for implementation in the learning process. 2) Implementation stage, covering the PBL syntax including problem orientation, organizing students, mentoring individual and group investigations, developing and presenting results and analyzing and evaluating the problem-solving process. 3) Evaluation stage, which is carried out in the form of formative assessments during the learning process. The results of this study provide a concrete picture of the effectiveness of the Problem Based Learning model as an innovative approach to creating more relevant, interactive, and student-centered Islamic Religious Education and Character Education learning, especially in dealing with contextual issues that require problem solving and moral reasoning.